Crystallization of Small Molecules in Microgravity Using Pharmaceutical In-Space Laboratory–Biocrystal Optimization eXperiment (PIL-BOX) - Lillian Miller; Molly K. Mulligan; Kenneth A. Savin; Stephen Tuma; Anne M. Wilson (Crystals, 2025)
Crystallization in microgravity has measurable benefits, from molecules as simple as sodium chloride to elaborate protein complexes. However, small organic molecules have not been reported. The small organic molecules glycine, famoxadone, carbamazepine, and 5-methyl-2-((2-nitrophenyl)amino)thiophene-3-carbonitrile (ROY) were crystallized on Earth under microgravity conditions. When comparing these different gravity crystallization conditions, we found the formation of different polymorphs and/or habits for glycine, carbamazepine, and ROY. The crystallization of famoxadone occurred more slowly in microgravity. The differences in size, appearance, and, in the case of ROY, color, are detailed in this report.